Molecular mechanism of neurodegeneration in spinal muscular atrophy - A. I. Vlasenko; V. D. Nazarov; S. V. Lapin; A. V. Mazing; E. A. Surkova; T. V. Blinova; M. P. Topuzova; T. M. Alekseeva (Нервно-мышечные болезни)
In the last decade, pathogenetic methods for the treatment of spinal muscular atrophy 5q have been developed. These include increased expression of the SMN2 gene, correction of SMN2 splicing, or reexpression of the SMN1 gene. Despite the comprehension of the genetic causes of the disease and the existence of therapies, it is still not completely known which molecular mechanisms in SMN protein deficiency lead to the degeneration of motor neurons. Understanding the molecular pathways involved in the loss of motor neurons may help develop new therapeutic strategies. The article presents genetic and biochemical data that reveal the molecular mechanisms of neurodegeneration in spinal muscular atrophy 5q.